Silicon as an acidity corrective associated with Azospirillum brasilense to improve nitrogen management and wheat profitability - Galindo, Fernando Shintate [UNESP]; Filho, Marcelo Carvalho Minhoto Teixeira [UNESP]; Buzetti, Salatiér [UNESP]; Rodrigues, Willian Lima [UNESP]; Boleta, Eduardo Henrique Marcandalli [UNESP]; Fernandes, Guilherme Carlos [UNESP] (Universidade Estadual de Londrina, 2020)
This research aimed to study a possible synergistic effect with inoculation with A. brasilense and N doses, associated with the application of silicon in acidity corrective form, evaluating the grain yield of irrigated wheat in Cerrado region. The experiment was conducted in Selvíria, MS, Brazil, under a no-till system, on a Latossolo Vermelho distrófico (Oxisol). The experiment was set up as a randomized block design with four replications, in a 2 × 5 × 2 factorial arrangement consisting of two soil corrective sources (dolomitic limestone and Ca and Mg silicate as source of Si); five N doses (0, 50, 100, 150, and 200 kg ha-1) applied in topdressing; and with and without inoculation with A. brasilense. Inoculation makes wheat production more profitable, irrespective of N doses and corrective sources. The N dose of 139 kg ha-1 with dolomitic limestone associated with inoculation of A. brasilense provided the greatest grain yield. However, the highest economic return was obtained at the N dose of 100 kg ha-1, with dolomitic limestone application and inoculation.
Keywords: Biological nitrogen fixation in grasses; Ca and Mg silicate; Plant growth-promoting bacteria; Total operational cost; Triticum aestivum L